The question of trust in the management of labour relations - Lopes, Albino (2003)
In shifting the focus of labour relations management away from the traditional unilateral and authoritarian form to the field of negotiated decision-making, the state has encouraged a debate with employers and unions which has not only borne fruit (agreement and social harmony), but has also become the source of legislation in the field of labour relations. With this process, the mistrust traditionally felt by the negotiating partners on the union side has, within each of the different political cultures of Western Europe, faded away.